2022
DOI: 10.3390/cancers14112593
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccination against Extracellular Vimentin Efficiently Adjuvanted with Montanide ISA 720/CpG

Abstract: Extracellular vimentin is a specific marker of the tumor vasculature, where it is secreted by tumor endothelial cells. Vaccination with a conjugate vaccine targeting extracellular vimentin was previously shown to induce a potent humoral immune response and tumor growth inhibition in mice. These data were obtained by vaccination using the toxic Freund’s adjuvant (FA) and are therefore not directly translatable into the clinic. In the present study, we aimed to investigate the potential of the biodegradable Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In principle, this procedure does not induce T cells against the target antigen. In a previous study by Van Loon et al, it was shown that this is indeed true for CD8 cells, while a moderate CD4 response was noted [17]. Therefore, we think that a similar response was generated in the dogs in our study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In principle, this procedure does not induce T cells against the target antigen. In a previous study by Van Loon et al, it was shown that this is indeed true for CD8 cells, while a moderate CD4 response was noted [17]. Therefore, we think that a similar response was generated in the dogs in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Passive targeting of eVim by monoclonal antibody therapy specifically and safely inhibited tumor growth in mouse melanoma and colorectal tumor models [14,15]. In order to induce endogenous antibody responses to self-antigens, we developed a novel conjugate vaccine technology, named iBoost [16,17] (Figure S1). Using iBoost vaccinations against eVim in mouse melanoma and colorectal carcinoma models, we observed potent anti-tumor responses characterized by reduced tumor growth, diminished tumor blood vessel density and a more favorable intratumoral immune cell composition [14].…”
Section: Introductionmentioning
confidence: 99%
“…developed a vimentin‐binding compound that efficiently inhibits cancer exosome release and reduces the mobility of cancer cells. In addition, vaccination with a conjugate vaccine targeting eVim has demonstrated significant tumor growth inhibition and decreased vessel density in the B16F10 melanoma tumor model 98 . Notably, in the treatment of dogs with bladder cancer, the use of the eVim‐targeted vaccine CVx1 in combination with meloxicam (a nonsteroidal anti‐inflammatory drug) resulted in nearly double the survival rate compared with a control group treated with carboplatin and piroxicam (another nonsteroidal anti‐inflammatory drug) 99 …”
Section: Potential Therapeutic Implications Of Targeting Extracellula...mentioning
confidence: 99%